Foundations of science mathematics, worked problems - D.S. Sivia (Oxford University Press, 1999)
With its companion volume, Foundations of Science Mathematics(Oxford Chemistry Primer 77), this book bridges the gap between high school and university-level maths. It provides solutions to most of the problems set in the companion volume and aims to bolster the reader's practical confidence by providing model answers, and additional comments, for a broad range of exercises. The informal tutorial style adopted in the principal text has been maintained and its concise nature makes it a useful reference for the experienced professional